Frugal innovation - Ratten, Vanessa (Innovation and technology horizons, 2019)
This book discusses the growing use and importance of frugal innovation in society. Frugal innovation looks at innovating in a cost-efficient manner by taking into account available resources. This book explains how frugal innovation is different to other types of innovation and how frugal innovation offers a creative solution to issues of sustainability and the circular economy. The book approaches innovation by taking into account the stakeholders and how companies can innovate efficiently in an inclusive manner. It presents successful cases of companies that have innovated frugally, making the book an engaging read for anyone who is interested to learn more